Fermi-edge singularities in the photoluminescence and magneto-optical spectra of modulation-doped v-groove quantum wires - Maciel, A; Kim, J; Davies, H; O'Sullivan, E; Ryan, J; Schwarz, A; Kaluza, A; Hardtdegen, H; Schapers, T; Meertens, D; Dieker, C; Luth, H (Elsevier, 2000)
We report the observation of strong Fermi-edge singularities photoluminescence spectrum the of strongly-confined, modulation-doped GaAs v-groove quantum wires. The behaviour of the singularity has been investigated at high excitation intensity, and both lattice and electrical heating. The latter produces a strong reduction of the singularity due to Fermi surface smearing, whereas, increased photoexcitation produces complex electron-hole correlation effects.